Participation and ICT: Students With Special Educational Needs in Upper Secondary School - Yngve, Moa (Linköping University Medical Dissertations, 2021)
Introduction: The use of information and communication technology (ICT) has been highlighted over the past 20 years as a promising accommodation to improve participation in school activities among students with special educational needs (SEN). However, evidence is still needed. In addition, little attention has been given to students opportunities for participation in school activities, their need for and access to support in school activities among students with SEN in upper secondary education. Aim: The overall aim of this thesis was to increase knowledge about the participation in school activities of students with special educational needs in regular upper secondary education before and after they received an ICT intervention, and subsequently their participation in productive occupations. Methods: This thesis comprises four studies in which secondary data from a sample of students with SEN in upper secondary education that had received an ICT intervention was used. Secondary data of students was retrieved from two intervention projects in which school personnel identified students with SEN based on the following criteria: difficulties in achieving educational goals, or completing school assignments and/or high levels of school absence. The first study included secondary data for 509 students with SEN who had given written informed consent to participate in the research. Of these, about forty percent did not have any educational support at inclusion. Based on the pool of 509 students, study-specific criteria was applied in three successive studies. Study I was a psychometric evaluation of the assessment instrument the School Setting Interview (SSI), which measures the student–environment fit and identifies students’ potential need for support in 16 school activities. Rasch analysis was used to examine the targeting, model fit, functioning of items and response categories, and unidimensionality of the SSI scale. Study II used descriptive statistics to examine the perceived need for, and access to, support in school activities among 484 students. In addition, a logistic regression analysis was applied to identify factors associated with students who perceived a need for support in school activities to the highest extent. In study III, the influence of an individualised ICT intervention on participation in school activities was evaluated among 300 students with SEN. Descriptive statistics were used to analyse students SSI assessments before and after the intervention, their school attendance, and pass grades. A Wilcoxon’s signed-rank test and a t-test investigated differences in support needs and the interval measure of student–environment fit, generated via Rasch analysis, before and after the ICT intervention. Chi-square analyses and t-tests were performed to investigate differences between students who had and had not achieved a significant improvement in student–environment fit after the intervention. Study IV applied an embedded mixed-methods approach. Participants who had agreed during study III to be contacted one year after upper secondary education (n = 244) received a questionnaire to investigate their participation in productive occupations. Eighty-one answered the questionnaire. In addition, 20 participated in a semi-structured interview using the Swedish version of the Worker Role Interview (WRI) to investigate their perceived work ability. Data from the questionnaire and the participants’ WRI ratings were analysed using descriptive statistics, and group comparisons were performed between participants who were and were not established in productive occupations. Written notes from the WRI rating forms were analysed using a deductive content analysis. Findings: The students with SEN perceived a need for support in several school activities (Mdn 7) and were rarely satisfied with the support that the school had provided (study II). It was demonstrated that the academic school activities: Remember things, Write, Do homework, Read and Take exams, in which more than two-thirds of the students perceived a need for support, were in need of most improvements to promote students’ participation. Study II further showed that students with a high level of school absence, enrolled in a vocational programme or with a neuropsychiatric disorder were those who perceived the greatest need for support in school activities. The psychometric evaluation of the SSI in study I provided support for the construct validity of the SSI for measuring the student–environment fit among students with SEN in upper secondary education. Furthermore, the analysis revealed that the rating categories of the scale did not function as intended which led to a post hoc categorisation of items with disordered thresholds in Study III in order to obtain reliable measurements of student– environment fit before and after the ICT intervention. Study III showed that an individualised ICT intervention, including computer, tablet and/or smartphone with software, and services to use the ICT as support in school activities, increased the student–environment fit. After the intervention, the decrease in students’ support needs and improved student–environment fit were found to be statistically significant with large effect sizes. Just over half of the students had increased or maintained their school attendance and obtained pass grades in all the courses in which they were enrolled in English, Mathematics and Swedish. The ICT intervention proved to be most beneficial for students who experienced fewer than the median number of support needs in school activities (Mdn 6), who had been without previous support in school and for students with pass grades. One year after upper secondary education, almost two-thirds (63%) of the participating 81 former students with SEN were either working or enrolled in further studies. The group that was established in work or further studies had obtained pass grades in all subjects to a greater extent and had received time-assisting ICT to a lesser extent during the intervention in their upper secondary education than the group that was not established (study IV). The former students with SEN believed in their work ability and were optimistic and motivated about future work or studies. During the process of finding and obtaining a productive role as an employee or student, the participants perceived social support from friends and family. Conclusion: This thesis demonstrated restricted participation in several school activities among the students with SEN in upper secondary education and students were rarely satisfied with the support that the school had provided. Findings indicated that the academic school activities: Remember things, Write, Do homework, Read and Take exams were in need of most improvements to promote participation among students with SEN. Attention should also be given to identifying the need for support in school activities among students with a high level of school absence, enrolled in vocational programmes or with a neuropsychiatric disorder. In this process, the SSI can be used as a valid assessment instrument. An individualised ICT intervention has the potential to provide students with SEN better opportunities to participate in school activities. Findings also indicated that the former upper secondary school students with SEN who had received an individualised ICT intervention had belief in their work ability.